2008
DOI: 10.1089/thy.2007.0262
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Year-Old Boy with a Suspicious Thyroid Nodule: Intrathyroidal Thymic Tissue

Abstract: Ectopic thymus tissue should be considered in the differential diagnosis of thyroid masses, especially in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…In an 11 year-old girl, a 5 year-old boy and a 6 year-old girl (Patients 1, 8 and 9), the lesion got slightly smaller. In a female patient with bilateral IET (Patient 13), the lesion on the right was slightly smaller by age 10, whereas the le- 1 Longitudinal x AP x transverse; if only 2 dimensions are given transverse x AP; 2 Respectively; side, craniocaudal location as described in methods, anteroposterior location as described in methods; 3 All lesions were hypoechoic compared to surrounding thyroid, had well defined borders and were identical in sonographic appearance to normal thymus of the patient; 4 Underwent fine-needle aspiration; cytologic diagnosis was IET. The echogenicity of the lesion increased during follow-up; 3 Underwent hemithyroidectomy; pathologic diagnosis was IET; 6 Lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an 11 year-old girl, a 5 year-old boy and a 6 year-old girl (Patients 1, 8 and 9), the lesion got slightly smaller. In a female patient with bilateral IET (Patient 13), the lesion on the right was slightly smaller by age 10, whereas the le- 1 Longitudinal x AP x transverse; if only 2 dimensions are given transverse x AP; 2 Respectively; side, craniocaudal location as described in methods, anteroposterior location as described in methods; 3 All lesions were hypoechoic compared to surrounding thyroid, had well defined borders and were identical in sonographic appearance to normal thymus of the patient; 4 Underwent fine-needle aspiration; cytologic diagnosis was IET. The echogenicity of the lesion increased during follow-up; 3 Underwent hemithyroidectomy; pathologic diagnosis was IET; 6 Lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Sonographic differential diagnosis also includes parathyroid adenomas and nodular type of Hashimoto thyroiditis [4]. Further complicating the matter is that, since the aspirate from IET would contain lymphoid cells, the cytologist might evaluate it as Hashimoto's thyroiditis or even thyroid lymphoma [3,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also reported an additional patient who underwent thyroid lobectomy because the ectopic thymus was thought to be a tumor [16]. Ectopic intrathyroidal thymus rarely gives rise to symptoms [1,2,3,4,5,6,7]. In the majority of previously reported cases (table 2) the diagnosis of ectopic thymus was made after surgery and/or fine-needle aspiration biopsy because the thymic inclusion was thought to be a thyroid nodule.…”
Section: Discussionmentioning
confidence: 99%
“…When mistaken for a thyroid nodule, the finding of intrathyroidal ectopic thymic tissue may lead to surgery and/or invasive diagnostic procedures in children [1,2,3,4,5,6,7]. However, the thymus has a unique appearance on ultrasonography and ectopic thymus parenchyma can be easily identified [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%